Intentional Solidarity as a Decolonizing Practice - Ku, Jane (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2019)
This article conceptualizes what a border literate reading looks like through a re-reading of Sky Lee’s 1990 novel Disappearing Moon Café. Using postcolonial feminist understanding of transnational literacy, with the help of queer scholarship on intimacy, I explore the difficulty of seeing the intersectionality of struggles of Chinese Canadian and Indigenous women. I argue that a border literacy alone may not be enough to propel us towards investing in these encounters. A deliberate intentionality that is based on a desire for a specific kind of future is necessary in how we retrace the past and in turn give shape to a different solidarity in the present that is not based only on the needs of the ally but a vulnerability and openness for new knowledges and different ways of being.